الخطر في عقد تأمين المشاريع النفطية: دراسة مقارنة - علي راقية عبد الجبار; محمد بشرى رضا (Journal of Legal Sciences, 2019)
The insured risk is the inherent characteristic of the oil industry from other industries. This is due to the nature of the circulating materials in it and their capability to quick burning and complicating the manufacturing operations which require caution when dealing with them at all stages starting from the upstream, i.e. the search stage, and drilling and then extracting oil until reaching the downstream stage and sending the product to the consumer. Those implementation of oil projects are characterized by their high cost which as a result leads to high loss scale if the risk occurs, and in turn to high compensation amount of money. Thus, the foreign companies executing oil projects should search for means of protecting their capitals by having an insurance coverage against the risks possible to occur so as to secure the compensation for the losses that may occur due to accidents.